Microarray analyses of lncRNAs and mRNAs expression profiling associated with diabetic peripheral neuropathy in rats. Issue 9 (26th April 2019) - Guo, Guojun; Ren, Sen; Kang, Yu; Liu, Yutian; Duscher, Dominik; Machens, Hans‐Günther; Chen, Zhenbing
Abstract: Diabetic peripheral neuropathy (DPN) is considered to be the most frequent neuropathic complication of diabetes, and severely affects the quality of life of patients. Long noncoding RNAs (lncRNAs) participate in various pathophysiological processes and associate with many diseases. However, the exact impact of lncRNAs on DPN remains obscure. To discover a potential connection, a microarray study was conducted to analyze the expression profiling of lncRNAs and messenger RNAs (mRNAs) in dorsal root ganglia (DRG) from streptozotocin‐induced diabetic rats with DPN. As a result, 983 lncRNAs and 1357 mRNAs were aberrantly expressed compared with control samples. Using bioinformatics analyses, we identified 558 Gene Ontology terms and 94 Kyoto Encyclopedia of Genes and Genomes pathways to be significantly enriched. Additionally, the signal‐net analysis indicated that integrin receptors, including Itgb3, Itgb1, Itgb8, and Itga6, might be important players in network regulation. Furthermore, the lncRNA‐mRNA network analysis showed dynamic interactions between the dysregulated lncRNAs and mRNAs. This is the first study to present an overview of lncRNA and mRNA expressions in DRG tissues from DPN rats. Our results indicate that these differentially expressed lncRNAs may have crucial roles in pathological processes of DPN by regulating their coexpressed mRNAs. The data may provide novel targets for future studies, which should focus on validating their roles in the progression of DPN. Abstract : Using microarray analysis, a total of 983 lncRNAs and 1357 mRNAs were found to be aberrantly expressed in DRG tissues from streptozotocin (STZ)‐induced diabetic rats, taking normal Sprague‐Dawley (SD) rats as controls. The lncRNA‐mRNA coexpression network analysis revealed that the dysregulated lncRNAs could interact with the dysregulated mRNAs, to participate in the development of diabetic peripheral neuropathy.